Pelatihan Dasar Microsoft Office Bagi Remaja Putus Sekolah Sebagai Upaya Pemberdayaan Digital - Edi Tohidi; Dodi Solihudin; Mochamad Arief Saputra; Mochammad Haris Maulana Ibrahim (CV. Multi Kreasi Media, 2023)
Basic skills in using Microsoft Office applications are essential competencies for enhancing job opportunities and participation in various activities in the digital era, especially for out-of-school youth who often have limited access to formal education. This Community Partnership Program aims to empower out-of-school youth through basic Microsoft Office training. This training is designed to provide understanding and practical skills in using Microsoft Word for document processing, Microsoft Excel for data processing and simple calculations, and Microsoft PowerPoint for creating presentations. It is expected that, through this training, out-of-school youth can improve their functional skills, open opportunities for jobs requiring basic administrative abilities, and increase their self-confidence in facing the challenges of the digital era.